Development of an in-vitro epithelial-myofibroblast intestinal model - Patient, J.D. (2016)
In vitro studies of drug permeability are traditionally carried out using cultured monolayers of epithelial cell lines grown on semi permeable membranes. Caco-2 cells, which are colon-derived, spontaneously form polarised cell layers when cultured in vitro which are akin to an epithelium of enterocyte-like cells. The Caco-2 model has been developed as a powerful in vitro tool in the early assessment of human drug permeability and is even approved by regulatory agencies for biowaver applications (i.e. in vitro tests in lieu of in vivo animal experiments).